Temperature- and genotype-dependent stress response and activation of the hypothalamus-pituitary-interrenal axis during temperature-induced sex reversal in pejerrey Odontesthes bonariensis, a species with genotypic and environmental sex determination - Torres Martínez, Aarón (2024)
In the pejerrey Odontesthes bonariensis (Atheriniformes, Atherinopsidae), exposure to high andlow temperatures during the critical period of sex determination (CPSD) induce testicular and ovarian differentiation, respectively, regardless of the presence or not of the sex determining gene amhy, which is crucial for testis formation only at intermediate, sexually neutral temperatures. In this study we explored the existence of genotype-specific signaling of Crh (Corticotropin Releasing Hormone) family genes and their associated carrier protein, receptors, and other stress-related genes in response to temperature during the CPSD and the potential involvement of the central nervous system via the hypothalamus-pituitary-interrenal (HPI) axis in sex determination of this species. The Crh family genes crhb, uts1, ucn3, the receptor crhr1 and the stress-related genes gr1, gr2, nr3c2 were transiently upregulated in the heads of pejerrey larvae during the CPSD by high temperature alone or in combination with other factors. Only crhr2 transcript abundance was not influenced by temperature but independently by time and genotype. In most cases, mRNA abundance was higher in the XX heads compared to that of XY individuals. XX larvae also showed higher whole-body cortisol titers than the XY, downregulation of cyp19a1a and upregulation of the testis-related genes amhy/amha in trunks (gonads) and were 100% masculinized at the high temperature.In contrast, at the low temperature, crhbp and avt were upregulated in the heads, particularly the former in XY larvae. cyp19a1a and amhy/amha were up- and downregulated, respectively, in the gonads, and fish were 100% feminized. Signaling via the HPI axis was observed simultaneously with the first molecular signs of ongoing sex determination/differentiation in the gonads. Overall, the results strongly suggest a temperature-dependent, genotype-specific regulatory action of the brain involving the Crh family of stress-related genes on the process of environmental sex determination of pejerrey.